Components of Participatory Engagement within E-Learning Community - Noor Hida Natrah Aziz; Haryani Haron; Afdallyna Fathiyah Harun (Institute of Advanced Engineering and Science, 2018)
This paper explores the components of participatory engagement to improve learner’s engagement within the e-learning community. Data are gathered through observations to measuring the interactions of the learner’s. The measurement included the learners’ feedbacks through the interactions of learners and educators, learners and learners and learners and content. Follow-up interviews are conducted to get deeper insights into the interactions and overall learner’s engagement environment. Findings show that in order to promote learners’ engagement in e-learning components such as accessibility, mobility, active learning and collaboration must be present in an e-learning ecosystem.